2022
DOI: 10.1126/science.abi9810
|View full text |Cite
|
Sign up to set email alerts
|

Live-cell micromanipulation of a genomic locus reveals interphase chromatin mechanics

Abstract: Our understanding of the physical principles organizing the genome in the nucleus is limited by the lack of tools to directly exert and measure forces on interphase chromosomes in vivo and probe their material nature. Here, we introduce an approach to actively manipulate a genomic locus using controlled magnetic forces inside the nucleus of a living human cell. We observed viscoelastic displacements over micrometers within minutes in response to near-piconewton forces, which are consistent with a Rouse polymer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 49 publications
6
40
0
Order By: Relevance
“…However, in the picture of higher-order catalysis, the multi-way contacts come and go quickly, rearranging chromatin constantly. Such nonequilibrium activities allow chromatin to stay in a highly dynamic, liquid-like state, which is consistent with recent experimental observations 58 .…”
Section: Discussionsupporting
confidence: 91%
“…However, in the picture of higher-order catalysis, the multi-way contacts come and go quickly, rearranging chromatin constantly. Such nonequilibrium activities allow chromatin to stay in a highly dynamic, liquid-like state, which is consistent with recent experimental observations 58 .…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, our previous work has shown that removal of cytoskeletal forces does not cause relaxation of the nucleus to a spherical morphology, implying nuclear deformations in spread cells are irreversible [38]. Consistent with these findings, elastic forces in the nuclear interior have been found to rapidly dissipate on the time scale of seconds and that the nuclear contents behave as a viscous fluid on this time scale [45; 46]. From literature estimates of the area dilation modulus (∼390 nN/µm; [47]), the nuclear bulk modulus (∼5 nN/µm 2 [48]), and the cortical tension (∼0.5 nN/µm; [42]), the areal extension of the lamina and changes in volume due to compression in the flattened nucleus during spreading are expected to be less than 1%, based on pressures and tensions calculated from Eq.…”
Section: Discussionmentioning
confidence: 57%
“…Our model could thus be applicable to chromatin, which shows a much larger cell-to-cell variability than stable protein structures (88, 89). In this context, we zoom out to large length scales where chromatin behaves like a Rouse polymer (9092), and molecular drivers of active processes [Fig. 1] produce effective athermal excitations.…”
Section: Discussionmentioning
confidence: 99%